Carbon- Nanotube- Modifi ed Electrodes for Highly Effi cient Acute Neural Recording - Shin, Jung Hwal; Kim, Guk Bae; Lee, Eun Joo; An, Taechang; Shin, Kumjae; Lee, Seung Eun; Choi, WooSeok; Lee, Sukchan; Latchoumane, Charles; Shin, Hee-Sup; Lim, Geunbae (WILEY, 2014)
Microelectrodes are widely used for monitoring neural activities in various neurobiological studies. The size of the neural electrode is an important factor in determining the signal-to-noise ratio (SNR) of recorded neural signals and, thereby, the recording sensitivity. Here, it is demonstrated that commercial tungsten microelectrodes can be modified with carbon nanotubes (CNTs), resulting in a highly sensitive recording ability. The impedance with the respect to surface area of the CNT-modified electrodes (CNEs) is much less than that of tungsten microelectrodes because of their large electrochemical surface area (ESA). In addition, the noise level of neural signals recorded by CNEs is significantly less. Thus, the SNR is greater than that obtained using tungsten microelectrodes. Importantly, when applied in a mouse brain in vivo, the CNEs can detect action potentials five times more efficiently than tungsten microelectrodes. This technique provides a significant advance in the recording of neural signals, especially in brain regions with sparse neuronal densities.